Finite element analysis of mechanical coupling using ANSYS - Chia, Kim Heng (Nanyang Technological University, 2021)
Mechanical couplings are broadly utilised in connection with two spinning parts such as blowers, gas turbines, and aviation applications as a result of their capacity to deliver force and their ensuing ability to remunerate misalignment in practically all directions. Transmit rotational motion and torque from driver part to driven part are the primary function of mechanical coupling. The unforeseen factors such as imbalance mass response and solidness of bearing support in the coupling system could bring rotor vibration. Analysis of the elements affecting the rotor vibrations because of bearing solidness and imbalance mass response will assist with improving the plan and control of a rotor dynamic in a mechanical coupling system. In this paper, a flexible coupling 3D will be modelled to perform these analyses. In the research, the natural frequency, critical speed, and unbalance mass response of the coupling were studied. Finite Element Analyse by utilising ANSYS to study the behaviour of vibration amplitude with respect to bearing solidness and unbalance mass response. The FEA results showed that bearing solidness immensely affected the vibration amplitude and critical speed. At last, ends were conveyed dependent on these outcomes, and further research extension was proposed.